(untitled) (Eureka Journal of Humanities and Social Research, 2026)
Every change that occurs in the lives of young people affects the formation of their human qualities and their development as complete individuals. The role of interpersonal relationships in the formation of spiritual values, the inner spirit of a person (nation), their intelligence, their self-awareness, the fullness of good deeds and noble intentions is of great importance.